Living Day by Day - Rachel L. Kaplan; Cynthia El Khoury; Emily R. S. Field; Jacques Mokhbat (SAGE Publishing, 2016)
We examined the meaning of living with HIV/AIDS among women in Lebanon. Ten women living with HIV/AIDS (WLWHA) described their experiences via semistructured in-depth interviews. They navigated a process of HIV diagnosis acceptance that incorporated six overlapping elements: receiving the news, accessing care, starting treatment, navigating disclosure decisions, negotiating stigma, and maintaining stability. Through these elements, we provide a framework for understanding three major themes that were constructed during data analysis: Stand by my side: Decisions of disclosure; Being "sick" and feeling "normal": Interacting with self, others, and society; and Living day by day: focusing on the present. We contribute to the existing literature by providing a theoretical framework for understanding the process of diagnosis and sero-status acceptance among WLWHA. This was the first study of its kind to examine the meaning of living with HIV/AIDS among women in a Middle Eastern country.